2015
DOI: 10.3892/ijo.2015.3164
|View full text |Cite
|
Sign up to set email alerts
|

SCTR regulates cell cycle-related genes toward anti-proliferation in normal breast cells while having pro-proliferation activity in breast cancer cells

Abstract: Secretin receptor (SCTR), the G-protein coupled receptor (GPCR) for secretin, has been observed to be upregulated in a few tumor types while downregulated in others, promoting or suppressing the proliferation of tumor cells, respectively. However, little is known about the molecular regulatory mechanism of dysregulation in cancer. In the present study, an analysis of the biological pathways affected by methylation in breast cancer using the methylome databases revealed that GPCRs played a major part in the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In physiological conditions, SCT binds to * * its receptor to mediate the effect of the gastrointestinal hormone on digestion and water homeostasis. e overexpression of SCT in MCF-7 cells led to an increase of the cell proliferation index and cellular migration [44]. e data of this study revealed the fact that miR-214-3p inversely acted on SCT in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In physiological conditions, SCT binds to * * its receptor to mediate the effect of the gastrointestinal hormone on digestion and water homeostasis. e overexpression of SCT in MCF-7 cells led to an increase of the cell proliferation index and cellular migration [44]. e data of this study revealed the fact that miR-214-3p inversely acted on SCT in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 54%
“…However, whether SCT is an oncogene or a tumor suppressor is still controversial. A number of studies hold the idea that it is an oncogene, as high expression was observed in breast cancer [44], whereas other studies indicated the downregulation of the gene in colorectal cancer [45] and prostate cancer [46]. SCT acts as a gene with double-edge sword activities, which possesses both oncogenic and tumorsuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulated GPCRs that have been proposed as therapeutic targets in cancer included the adenosine receptors ADORA1 and ADORA3 , and important GPCRs for autocrine growth factors in cancer, such as bombesin receptor NMBR , and neurotensin receptor NTSR1 45 , 46 . Additional GPCRs reported to promote proliferation and migration of cancer cells included secretin receptor SCTR , and lysophosphatidic acid (LPA) receptor LPAR2 47 , 48 . Finally, several upregulated hormone receptors were associated with the neuroactive receptor interaction pathway, including those for melanin-concentrating hormone, thyroid-stimulating hormone, calcitonin, corticotrophin-releasing hormone, follicle-stimulating hormone, luteinizing hormone beta, and glucagon-like peptide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…an oncogene with an anti-proliferative effect in normal cells but a proliferation-stimulating activity in cancer cells (64). BBR was also found to exhibit its antitumor effects in MCF-7 and MDA-MB-231 BC cells via upregulating tumor suppressor microRNA (miR)-214-3p and reducing SCT level (63, 64).…”
Section: Dna Tata Box and Poly(a) Tailsmentioning
confidence: 99%